2022
DOI: 10.15562/bmj.v11i3.3844
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of osteocyte in dental socket bone regenerative induced by hydroxyapatite bovine tooth graft

Abstract: Background: Tooth extraction is a procedure with the highest prevalence of causing alveolar bone damage. After extraction, the dimension will change. This procedure needs a balance of bone formation and resorption. Osteocytes are the most common cells in bone and have an essential role in bone formation. This study explores the effect of bovine tooth grafts on the number of osteocytes in the socket preservation process post-dental extraction. Methods: A total of 28 Wistar rats, 14 control and 14 treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…32 The normal wound healing process will increase the thickness of collagen when entering the proliferative phase and release growth factors to stimulate the proliferative activity of osteoblast cells, which in turn will induce osteocyte cells in wound healing. 33,31 In this study, the BAM application group had higher collagen thickness, number of osteoblasts, and osteocytes compared to the control group. This is because BAM, in the form of a sponge, contains collagen, which can absorb blood, so that bleeding wounds stop more quickly and speed up the haemostasis and coagulation phases.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…32 The normal wound healing process will increase the thickness of collagen when entering the proliferative phase and release growth factors to stimulate the proliferative activity of osteoblast cells, which in turn will induce osteocyte cells in wound healing. 33,31 In this study, the BAM application group had higher collagen thickness, number of osteoblasts, and osteocytes compared to the control group. This is because BAM, in the form of a sponge, contains collagen, which can absorb blood, so that bleeding wounds stop more quickly and speed up the haemostasis and coagulation phases.…”
Section: Discussionmentioning
confidence: 56%
“…This is indicated by the fact that the number of osteocyte cells has increased compared to osteoblast cells. 15 Zubaidah et al 31 , stated that osteocytes also showed that osteocytes started to grow on the 14 th day after the evaluation, and they kept growing for another 28 days following the application of hydroxyapatite bovine tooth graft and PEG as the carrier. Thus, osteoblast and osteocytes as components of bone regeneration are also inducing bone healing.…”
Section: Discussionmentioning
confidence: 99%
“… 12 13 14 15 Bovine-based HA is among the most applied bone grafts besides sintered HA due to their biocompatibility and osteoconductivity. 16 17 18 19 The main drawback of bovine HA and sintered HA is their slow resorption during implantation. This study attempted to fabricate nonsintered HA to improve resorption.…”
Section: Discussionmentioning
confidence: 99%